HUBUNGAN DISIPLIN KERJA DAN MOTIVASI KERJA DENGAN KOMITMEN ORGANISASIONAL DI LINGKUNGAN DINAS PENDIDIKAN KOTA BOGOR - Neneng Nita Granita Utami; Mohammad Entang; Radjab Tampubolon (Universitas Pakuan, 2019)
The purpose of this research is to know the correlation of work discipline and work motivation with organizational commitment in Education Department of Bogor City. The study population was 153 people with a total sample of 111 people determined using Slovin formula. Primary data collection using questionnaires and secondary data using recording. Data analysis techniques used descriptive statistical analysis techniques and correlational statistical analysis techniques. The research results are as follows: (1) There is a positive and significant correlation between work discipline with organizational commitment with correlation coefficient ry.1 = 0.519 and functional relationship Ŷ = 88.073 + 0.453X1. Contribution of work discipline to organizational commitment equal to 27.0%., (2) There is a significant positive relationship between work motivation with organizational commitment with correlation coefficient ry.2 = 0.749 and functional relationship Ŷ = 75.975 + 0.637X2. Contribution of work motivation to organizational commitment equal to 56.1%, and (3) There is a significant positive correlation between work discipline and work motivation together with organizational commitment with correlation coefficient r = 0.806 and functional relation Ŷ = 81.940 + 0.274X1 + 0.620X2. The contribution of work discipline and work motivation collectively to organizational commitment is 64.9%.